Two-dimensional coupled electro-optic delayed feedback system with varying parameters. Issue 6 (26th March 2017) - Liu, Lingfeng; Miao, Suoxia; Cheng, Mengfan; Gao, Xiaojing
Abstract: In this paper, a two-dimensional coupled electro-optic delayed feedback system with varying parameters is proposed. The phase diagram, bifurcation diagram, approximate entropy and permutation entropy are used for illustrating its dynamics performances. Results show that this system has a high complexity compared to other systems. Furthermore, this system can conceal the time delay effectively against the auto-correlation function, delayed mutual information and permutation information analysis method, which greatly improve the security performance. Summarily, our model is more complex and can conceal the time delay with a lower gain coefficient compared to the other proposed proposals.